Adsorption of extracellular lipase in a packed-bed reactor: an alternative immobilization approach - Freitas, Amanda Noli [UNESP]; Remonatto, Daniela [UNESP]; Miotti Junior, Rodney Helder [UNESP]; do Nascimento, João Francisco Cabral [UNESP]; da Silva Moura, Adriana Candido [UNESP]; de Carvalho Santos Ebinuma, Valéria [UNESP]; de Paula, Ariela Veloso [UNESP] (Springer Nature, 2024)
In light of the growing demand for novel biocatalysts and enzyme production methods, this study aimed to evaluate the potential of Aspergillus tubingensis for producing lipase under submerged culture investigating the influence of culture time and inducer treatment. Moreover, this study also investigated conditions for the immobilization of A. tubingensis lipase by physical adsorption on styrene–divinylbenzene beads (Diaion HP-20), for these conditions to be applied to an alternative immobilization system with a packed-bed reactor. Furthermore, A. tubingensis lipase and its immobilized derivative were characterized in terms of their optimal ranges of pH and temperature. A. tubingensis was shown to be a good producer of lipase, obviating the need for inducer addition. The enzyme extract had a hydrolytic activity of 23 U mL−1 and achieved better performance in the pH range of 7.5 to 9.0 and in the temperature range of 20 to 50 °C. The proposed immobilization system was effective, yielding an immobilized derivative with enhanced hydrolytic activity (35 U g−1), optimum activity over a broader pH range (5.6 to 8.4), and increased tolerance to high temperatures (40 to 60 ℃). This research represents a first step toward lipase production from A. tubingensis under a submerged culture and the development of an alternative immobilization system with a packed-bed reactor. The proposed system holds promise for saving time and resources in future industrial applications.
Keywords: Adsorption; Characterization; Enzyme; Immobilization; Packed bed reactor